Geospatial and Environmental Analysis of Stunting Prevalence in Pekanbaru City, Indonesia - Riska Epina Hayu; Eva Mayasari; Nur Hadziqoh (Jurnal Kesehatan Manarang, 2025)
Stunting is a chronic nutritional problem that remains a major public health challenge in Indonesia. In 2022, the national stunting prevalence was recorded at 21.6%, exceeding the WHO threshold of below 20%. In Pekanbaru, the prevalence reached 23%, contributing significantly to the total number of stunting cases in Riau Province. Stunting reflects the socio-economic conditions of a community, as it can be influenced by various factors, including population density and environmental conditions. This study aimed to analyze the spatial distribution of stunting in Pekanbaru and examine its correlation with environmental and geographic factors, including population density, access to clean water, and sanitation facilities. An observational analytical design was used, incorporating spatial analysis and correlation tests. The study was conducted in 2023 by confirming reported stunting cases. Results showed that stunting was distributed across 15 districts in Pekanbaru, with the highest prevalence found in the sub-districts of Lima Puluh. Notably, Lima Puluh also ranked third in population density. The average percentage of clean drinking water quality was 91.8%, and access to healthy latrines averaged 99.8%. Correlation analysis revealed no significant relationship between population density (p 0.112, r 0.417), drinking water quality (p 0.568, r 0.160), or access to healthy latrines (p 0.995, r 0.002) and the prevalence of stunting. These findings suggest that the three examined variables were not significantly associated with stunting incidence. However, the variable of population density showed a potential correlation, indicating a need for further research.